Social support compared with life satisafaction of patients with ischemic heart disease - Glińska, Jolanta; Cezak, Elżbieta; Lewandowska, Małgorzta; Brosowska, Beata (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Introduction. Ischemic heart disease is one of the key cause of reduced quality of life and premature mortality. It is seen as a state of disturbing the balance between the individual and the environment which leads suffers to look for social support. Aim. Aim of the study was assessment of the level of social support among patients with ischemic heart disease and analysis of the relationship between social support received and the level of life satisfaction. Material and methods. The study was conducted in 2012 at the Cardiology Unit in Łódź among 100 patients. To assess social support Social Support Scale was used. Whereas to measure life satisfaction with Life Scale was used. Results. Overall analysis of the data shows that the dominant group of respondents (72%) received more than 199 points, which indicates a high level of social support. According to the Satisfaction with Life Scale, the largest group (38%) consist of people of average life satisfaction (5–6 stents). The second position took people with a high sense of happiness (36%). Conclusions. More than three-quarters of patients with ischemic heart disease can count on a high level of social support. There is a small but positive correlation between social support and life satisfaction.